A NUMERICAL APPLICATION TO PREDICT THE RESISTANCE AND WAVE PATTERN OF KRISO CONTAINER SHIP - Ozdemir, Yavuz Hakan; Cosgun, Taner; Dogrul, Ali; Barlas, Baris (Brodarski Inst, 2016)
In this study, the computational results for KRISO Container Ship (KCS) are presented. CFD analyses are performed to simulate free surface flow around KCS by using RANS approach with success. Also the complicated turbulent flow zone behind the ship is well simulated. The RANS equations and the non-linear free surface boundary conditions are discretized by means of a finite volume scheme. The numerical methodology is found to be appropriate for simulating the turbulent flow around a ship in order to estimate ship total resistance and free surface. By the numerical results, total resistance is calculated for the ship model and the result is satisfactory with regard to the experimental one. As a result of well captured free surface, the wave elevation on/around the hull is compared with the experimental results.
Keywords: Computational Fluid Dynamics (Cfd); Turbulent Free Surface Flows; Wave Cut; Ship Resistance; Kcs